Avaliação da modulação dos níveis de hemoglobina fetal em crianças com anemia falciforme triadas pelo Programa de Triagem Neonatal de Minas Gerais e acompanhadas no Hemocentro de Belo Horizonte da Fundação Hemominas - Rahyssa Rodrigues Sales (2017)
Introduction: The clinical features of sickle cell anemia (SCA) are derived from the polymerization of deoxy-Hb S that causes a pathophysiological cascade. Fetal hemoglobin (Hb F) inhibits this polymerization, leading to a milder disease. Polymorphisms at quantitative inheritance loci (QTL) have been associated with Hb F levels. This study aimed to evaluate associations between HBBP1, BCL11A and intergenic HBS1L-MYB and the relative concentration of Hb F, as well as other hematological parameters in children with SCA. Materials and Methods: This is a retrospective cohort study involving children born between 1999 and 2008, with SCA confirmed by molecular techniques, screened by Newborn Screening Program of Minas Gerais state and followed-up at the Blood Center of Belo Horizonte. Polymorphism genotyping was performed by PCR-RFLP, sequencing or real-time PCR. Relative Hb F concentration was determined by hemoglobin electrophoresis at alkaline pH. Associations between the nominal variables were performed by the chisquare test or Fisher's exact test. For the continuous variables with normal distribution, analyses were performed using T or ANOVA test; variables with nonnormal distribution were analyzed by Mann-Whitney or Kruskal-Wallis tests. Results: 233 children were analyzed, of which 119 (51.1%) were male. The mean follow-up period was 9.78 (± 0.18) years. No association between rs10128556 (HBBP1) and the relative concentration of Hb F (p>0.05) was found. The frequency of the T allele was extremely low (MAF = 0.001), as expected. Only three (1.3%) heterozygotes (CT) and no TT homozygotes were identified. Regarding BCL11A, rs4671393 (allele A) and rs11886868 (allele C) were significantly associated with increased concentration of Hb F (p<0.001 and p=0.008, respectively). Polymorphisms rs7557939, rs11886868 and rs4671393 were associated with increased total Hb (p0.001). Regarding HBS1L-MYB, all polymorphisms were associated with Hb F concentration. Polymorphisms rs9399137 and rs35786788 were in total linkage disequilibrium and their C and A alleles, respectively, were associated with increased Hb F (p=0.002) and total Hb (p=0.001) and decreased white blood cell count (p=0.004), reticulocytes (p=0.003) and platelets (p=0.04). SNPs rs4895441 (allele G) and rs9402686 (allele A) were associated with increased Hb F (p=0.001), total Hb (p ~ 0.001), and peripheral oxygen saturation (SpO2) (p=0.001 and 0.004, respectively). These polymorphisms were also associated with decreased reticulocyte counts (p=0.001). The rs9494145 polymorphism was significantly associated with increased Hb F (p = 0.006), total Hb (p=0.001) and SpO2 (p=0.01) and decreased white blood cell count (p=0.01) and reticulocytes (p=0.006) counts. The insertion/deletion (In/del) AACCC/AAAC was associated with increased Hb F and total Hb concentration (p=0.006) and decreased white blood cell count (p=0,03) and reticulocytes (p=0.01) count. On the other hand, no association was found between single-base substitution A>G at position 135097850 of HBS1L-MYB (rs not available) and Hb F concentration or other hematological parameter (p>0.05). Conclusions: This study showed for the first time the influence of BCL11A and HBS1L-MYB polymorphisms on Hb F concentration and other hematological parameters in pediatric population with SCA from Minas Gerais state. This results corroborates most of the previously published studies.